Si/Ge intermixing during Ge Stranski–Krastanov growth - Portavoce, Alain; Hoummada, Khalid; Ronda, Antoine; Mangelinck, Dominique; Berbezier, Isabelle (Beilstein Journal of Nanotechnology, 2014)
The Stranski–Krastanov growth of Ge islands on Si(001) has been widely studied. The morphology changes of Ge islands during growth, from nucleation to hut/island formation and growth, followed by hut-to-dome island transformation and dislocation nucleation of domes, have been well described, even at the atomic scale, using techniques such as scanning tunneling microscopy and transmission electron microscopy. Although it is known that these islands do not consist of pure Ge (due to Si/Ge intermixing), the composition of the Ge islands is not precisely known. In the present work, atom probe tomography was used to study the composition of buried dome islands at the atomic scale, in the three-dimensional space. The core of the island was shown to contain about 55 atom % Ge, while the Ge composition surrounding this core decreases rapidly in all directions in the islands to reach a Ge concentration of about 15 atom %. The Ge distribution in the islands follows a cylindrical symmetry and Ge segregation is observed only in the {113} facets of the islands. The Ge composition of the wetting layer is not homogeneous, varying from 5 to 30 atom %.
Keywords: atom probe tomography; germanium islands; Stranski–Krastanov growth

(untitled) - Voigtländer, B. (Surf. Sci. Rep., 2001)

(untitled) - Berbezier, I.; Ronda, A.; Portavoce, A. (J. Phys.: Condens. Matter, 2002)

(untitled) - Teichert, C. (Phys. Rep., 2002)

(untitled) - Stangl, J.; Holý, V.; Bauer, G. (Rev. Mod. Phys., 2004)

(untitled) - Baribeau, J.-M.; Wu, X.; Rowell, N. L.; Lockwood, D. J. (J. Phys.: Condens. Matter, 2006)

(untitled) - Berbezier, I.; Ronda, A. (Surf. Sci. Rep., 2009)

(untitled) - Portavoce, A.; Kammler, M.; Hull, R.; Reuter, M.; Ross, F. M. (Nanotechnology, 2006)

(untitled) - Volpi, F.; Portavoce, A.; Ronda, A.; Shi, Y.; Gay, J. M.; Berbezier, I. (Thin Solid Films, 2000)

(untitled) - Portavoce, A.; Berbezier, I.; Gas, P.; Ronda, A. (Phys. Rev. B, 2004)

(untitled) - Portavoce, A.; Kammler, M.; Hull, R.; Reuter, M. C.; Copel, M.; Ross, F. M. (Phys. Rev. B, 2004)

(untitled) - Portavoce, A.; Hull, R.; Reuter, M. C.; Ross, F. M. (Phys. Rev. B, 2007)

Lateral alignment of epitaxial quantum dots - Schmidt, O. G. (Springer, 2007)

(untitled) - Regelman, D. V.; Magidson, V.; Beserman, R.; Dettmer, K. (Thin Solid Films, 1998)

(untitled) - Liao, X. Z.; Zou, J.; Cockayne, D. J. H.; Jiang, Z. M.; Wang, X.; Leon, R. (Appl. Phys. Lett., 2000)

(untitled) - Stangl, J.; Daniel, A.; Holý, V.; Roch, T.; Bauer, G.; Kegel, I.; Metzger, T. H.; Wiebach, T.; Schmidt, O. G.; Eberl, K. (Appl. Phys. Lett., 2001)

(untitled) - Sonnet, P.; Kelires, P. C. (Phys. Rev. B, 2002)

(untitled) - Floyd, M.; Zhang, Y.; Driver, K. P.; Drucker, J.; Crozier, P. A.; Smith, D. J. (Appl. Phys. Lett., 2003)

(untitled) - Denker, U.; Stoffel, M.; Schmidt, O. G. (Phys. Rev. Lett., 2003)

(untitled) - Denker, U.; Sigg, H.; Schmidt, O. G. (Mater. Sci. Eng., B, 2003)

(untitled) - Sonnet, P.; Kelires, P. C. (Appl. Phys. Lett., 2004)

(untitled) - Denker, U.; Sigg, H.; Schmidt, O. G. (Appl. Surf. Sci., 2004)

(untitled) - Hadjisavvas, G.; Kelires, P. C. (Phys. Rev. B, 2005)

(untitled) - Lang, C.; Cockayne, D. J. H.; Nguyen-Manh, D. (Phys. Rev. B, 2005)

(untitled) - De Seta, M.; Capellini, G.; Di Gaspare, L.; Evangelisti, F.; D’Acapito, F. (J. Appl. Phys., 2006)

(untitled) - De Seta, M.; Capellini, G.; Evangelisti, F. (Phys. Rev. B, 2008)

(untitled) - Leite, M. S.; Malachias, A.; Kycia, S. W.; Kamins, T. I.; Williams, R. S.; Medeiros-Ribeiro, G. (Phys. Rev. Lett., 2008)

(untitled) - De Seta, M.; Capellini, G.; Evangelisti, F. (Superlattices Microstruct., 2009)

(untitled) - Leite, M. S.; Kamins, T. I.; Medeiros-Ribeiro, G. (Appl. Phys. Lett., 2009)

(untitled) - Montoro, L. A.; Leite, M. S.; Biggemann, D.; Peternella, F. G.; Batenburg, K. J.; Medeiros-Ribeiro, G.; Ramirez, A. J. (J. Phys. Chem. C, 2009)

(untitled) - Lee, S. W.; Lee, C.-H.; Chang, H. T.; Cheng, S. L.; Liu, C. W. (Thin Solid Films, 2009)

(untitled) - Ogawa, Y.; Toizumi, T.; Minami, F.; Baranov, A. V. (Phys. Rev. B, 2011)

(untitled) - Biasiol, G.; Heun, S. (Phys. Rep., 2011)

(untitled) - Georgiou, C.; Leontiou, T.; Kelires, P. C. (AIP Adv., 2014)

(untitled) - Portavoce, A.; Berbezier, I.; Ronda, A. (Phys. Rev. B, 2004)

(untitled) - Portavoce, A.; Hoummada, K.; Berbezier, I.; Ronda, A.; Mangelinck, D. (Appl. Phys. Lett., 2012)

Atom-Probe Tomography: The Local Electrode Atom Probe - Miller, M. K.; Forbes, R. G. (New York, 2014)

(untitled) - Thompson, K.; Lawrence, D.; Larson, D. J.; Olson, J. D.; Kelly, T. F.; Gorman, B. (Ultramicroscopy, 2007)

(untitled) - Miller, M. K.; Russell, K. F.; Thompson, G. B. (Ultramicroscopy, 2005)

(untitled) - Portavoce, A.; Ronda, A.; Berbezier, I. (Mater. Sci. Eng., B, 2002)

(untitled) - Malachias, A.; Schülli, T. U.; Medeiros-Ribeiro, G.; Cançado, L. G.; Stoffel, M.; Schmidt, O. G.; Metzger, T. H.; Magalhães-Paniago, R. (Phys. Rev. B, 2005)

(untitled) - LeGoues, F. K.; Kesan, V. P.; Iyer, S. S.; Tersoff, J.; Tromp, R. (Phys. Rev. Lett., 1990)

(untitled) - Vantarakis, G.; Remediakis, I. N.; Kelires, P. C. (Phys. Rev. Lett., 2012)